A Community Emergency Department Rotation for Pediatric Emergency Medicine Fellows: Development and Evaluation. Issue 12 (December 2021) - Langhan, Melissa L.; Woolf, Seth; Tiyyagura, Gunjan
Abstract : Objective: There have been increasing job opportunities for pediatric emergency medicine (PEM) specialists within community emergency departments (CEDs), where 90% of children receive emergency care. The majority of training for PEM fellows occurs in academic children's hospitals, which may expose fellows to different resources than CEDs. Our goals were to develop and to evaluate a CED rotation aimed at improving exposure to this care environment for PEM fellows. Methods: Kern's 6 steps of curriculum development served as our framework to identify the problem, conduct a needs assessment, develop goals and objectives, formulate an educational strategy, and then plan the implementation and evaluation. Discussion and buy-in among trainees and hospital leadership took place during rotation development. Informal and web-based surveys of PEM fellows and CED attendings evaluated the rotation and assessed participants' reactions, changes in knowledge, and changes in behavior. Results: The CED rotation was piloted at 1 PEM fellowship program over 2 years. Nine PEM fellows participated in the month-long rotation. The majority of participants reported that the rotation goals and objectives were met and that they acquired new skills and rated the CED rotation as good or excellent. Challenges to the CED rotation included lower patient acuity and distance to the CED. Conclusions: A new CED rotation was developed, piloted, and well received by participants. Given the potential differences in practice between tertiary care children's emergency departments and CEDs, as well as increasing job opportunities in CEDs, program directors should consider incorporating a CED rotation for their PEM fellows.